Pengaruh Platform Wordwall Berbasis Website dalam Meningkatkan Minat Belajar Peserta Didik pada Mata Pelajaran PAI - Syahidatil Maghfirah; Sulaiman Sulaiman (AS-SABIQUN, 2022)
This study aims to determine the effect of a website-based wordwall platform on students' interest in learning. The type of this research is quantitative with a pre-experimental method of design one shoot case study. The subjects of this study were students of class X TJKT SMK Negeri 2 Padang. The data collection instrument used was a questionnaire with additional supporting data such as observations, interviews and documentation. The results showed that 1) from the results of hypothesis testing using the t test, it was stated that t table > t arithmetic, namely 5.666 > 2.03951, with a significance value of 0.000 which means <0.05 this means that H1 is accepted and H0 is rejected. 2) based on the results of the f test, the results of f table > f count are 32.106 > 4.16, which means that the wordwall platform variable (x) has an influence on increasing the learning interest variable (y). 3) from the simple linear regression test the equation Y = 17,830 - 1,225X